DNAJC8: a prognostic marker and potential therapeutic target for hepatocellular carcinoma - Zhang, Zhibo; Ju, Mingxiu; Tang, Zhongming; He, Zhen; Hua, Shengni (Frontiers in Immunology, 2024)
Background: Hepatocellular carcinoma (HCC) is the most common type of liver cancer, accounting for ~90% of the total cases. DnaJ heat shock protein family member C8 (DNAJC8), belonging to the heat shock protein 40 (HSP40) family, is known to regulate cancer biology function. However, the role of DNAJC8 on HCC development remains unknown.The Cancer Genome Atlas, GTEx, cBioPortal, and Human Protein Atlas were used to analyze the expression and clinical significance of DNAJC8 in HCC. Two HCC cell lines, MHCC-97H and Huh-7, were utilized to determine the biological function of DNAJC8. Results: DNAJC8 expression was upregulated in HCC tissues and correlated with poor clinical prognosis. It was closely related to spliceosome, nucleocytoplasmic transport, and cell cycle and might be involved in the formation of tumor immunosuppressive microenvironment. Knockdown of DNAJC8 severely inhibited HCC cell proliferation and induced apoptosis.Our study demonstrate that DNAJC8 functions as an oncogene in HCC and hence may be used as a potential therapeutic target and prognostic marker for HCC.